Factors Influencing Entrepreneurial Intention Among Vocational Engineering Students: A Systematic Literature Review - Samuel Nnadoziem Ndukuba (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2026)
Over decades, entrepreneurial intention (EI) has been widely recognised as the most reliable antecedent of entrepreneurial behaviour. In vocational and technical higher education, understanding the determinants of EI is critical for developing curricula. Hence, producing graduates capable of creating employment rather than solely seeking a job. The systematic literature review (SLR) synthesises empirical evidence on the factors that influence entrepreneurial intention among students enrolled in vocational engineering education programmes. Most especially, focus on engineering contexts. A PRISMA 2020-compliant SLR was conducted across Scopus, Web of Science, and Emerald Insight databases. This covers peer-reviewed articles published between January 2020 and December 2025. Forty-two studies are meeting the eligibility criteria were included in the final synthesis. Hence, seven thematic factor clusters emerged: (1) entrepreneurship education and curriculum design, (2) entrepreneurial self-efficacy, (3) motivation and attitude, (4) risk-taking propensity, (5) industry internship and practical experience, (6) digital technology literacy and technopreneurship, and (7) social and family environment. The finding shows that Self-efficacy and entrepreneurship education were the most consistently supported factors across the included studies. Also, digital technology literacy emerged as a rising construct, remarkably relevant to engineering students. Those students are leveraging online marketplaces and social media for automotive business ventures. Lastly, vocational engineering programmes need to integrate teaching-factory models, technopreneurship training, and structured industry-linkage programmes to cultivate EI that will create job opportunities for unemployed youths.